Neutron Dosimetry for In Vitro Biomedical Sample Irradiations - Kalamara, A.; Stamatelatos, I.E.; Stefanopoulos, K.L.; Grigalavicious, M.; Theodossiou, T.; Lagoyannis, A. (HNPS Advances in Nuclear Physics, 2022)
The absorbed dose in vials containing photo-sensitizer solutions irradiated under neutron beams produced by the p-Li, D-D and D-T reactions was calculated. Monte Carlo simulations were performed by coupling the NeuSDesc and MCNP codes in order to derive the neutron energy spectrum, fluence and absorbed dose with depth in the samples. The absorbed dose was estimated taking into account the contributions of all particles (photons, electrons, protons and alpha particles). This study provides important information for the interpretation of in vitro irradiation experiments to be performed under the research program FRINGE aiming to investigate neutron generated electronic excitation as a foundation for a radically new cancer therapy.